Natuna dan Transformasi Eksternal Regional Security Supercomplexes Laut China Selatan - Mely Noviryani (Department of International Relations, Brawijaya University, 2014)
Abstract The South China Sea is territorial waters between East Asia and Southeast Asia disputed among China, Taiwan, Malaysia, Vietnam and the Philippines related to the annexation of the Spratly and Paracel islands.Based on Regional Security Complex Theory introduced by Barry Buzan and Ole Waever, the type of thesecurity complex as this is the type of Supercomplexes Regional Security where strong interregional security dynamics arising from great power spill over into adjacent regions. In the beginning of this article will be explained how Supercomplexes Regional Security in the South China Sea region. In further development, China is increasingly expanding its claim to the territory in the South China Sea by further claiming most of Natuna islands which belong to Indonesian territory by putting nine dash line on their map. Indonesia has thus far been a non-claimant state in the South China Sea conflict. Indonesia, instead, as ASEAN Member States takes part initiating mediation in this conflict. However, claim over Natunaislands istherefore pushing Indonesia becomes one of the claimant states. By applying Regional Security Complex Theory, it will observe that the involvement of Indonesia into the conflict is form of an external transformation of the Supercomplexes Regional Security Keywords : external transformation, Regional Security Complex Theory, South China Sea Conflict